2019
DOI: 10.2147/ccid.s220849
|View full text |Cite
|
Sign up to set email alerts
|

<p>Outbreaks And Epidemics Of Superficial Dermatophytosis Due To <em>Trichophyton mentagrophytes</em> Complex And <em>Microsporum canis</em>: Global And Indian Scenario</p>

Abstract: Until recently, superficial dermatophytosis, also known as tinea, was considered as a minor skin infection, which was easy to treat. There used to be rare outbreaks and epidemics of superficial dermatophytosis. Lately, there is a sweeping change in the clinical presentation due to extensive, atypical and recalcitrant dermatophytosis. Treating such infections poses a great challenge to the clinicians. Dermatophytosis is a superficial fungal infection of keratinized tissue (skin, hairs and nails) by dermatophyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…interdigitale species complex ( T. mentagrophytes genotype VIII) with a person to person transmission of this new strain type (genotype VIII) that was thought previously to be a zoophilic species. Also acquired antifungal treatment resistance, inappropriate use of topical therapy containing antimicrobial medication (antifungal and antibacterial) combined with potent corticosteroids and a possible altered immune response of the host is considered important 3,6,7 . Variable bioavailability of some generic antifungals may also contribute through underdosing during treatment.…”
Section: Introductionmentioning
confidence: 99%
“…interdigitale species complex ( T. mentagrophytes genotype VIII) with a person to person transmission of this new strain type (genotype VIII) that was thought previously to be a zoophilic species. Also acquired antifungal treatment resistance, inappropriate use of topical therapy containing antimicrobial medication (antifungal and antibacterial) combined with potent corticosteroids and a possible altered immune response of the host is considered important 3,6,7 . Variable bioavailability of some generic antifungals may also contribute through underdosing during treatment.…”
Section: Introductionmentioning
confidence: 99%
“…3,13 Presently, T. mentagrophytes and T. interdigitale are indistinguishable based on phenotypic and genotypic characteristics, due to which they are both described as T. mentagrophytes complex. 3,32,33 as T. tonsurans 24 and T. rubrum isolates with T. violaceum 18,34 has been previously reported suggesting a close relationship between these species. However, in our study, a distinct spectral profile was observed that could clearly distinguish T. mentagrophytes vs. T. tonsurans and T. rubrum vs. T. violaceum.…”
Section: Discussionmentioning
confidence: 74%
“…Frequent misidentification is a major issue with dermatophytes which may be due to the frequent changes in species name 3,13 . Presently, T. mentagrophytes and T. interdigitale are indistinguishable based on phenotypic and genotypic characteristics, due to which they are both described as T. mentagrophytes complex 3,32,33 . Thus, to avoid any confusion in the identification of T. mentagrophytes and T. interdigitale , we enriched our in‐house database as T. mentagrophytes complex.…”
Section: Discussionmentioning
confidence: 99%
“…21 Previously, outbreaks and epidemics were typically due to anthropophilic dermatophytes, but now, can also be seen due to zoophilic dermatophytes, e.g., T. mentagrophytes and M. canis. 67 In the past, differentiation of T. mentagrophytes (zoophilic species) from T. interdigitale (anthropophilic species) was not feasible, but molecular typing has solved this problem.…”
Section: Discussionmentioning
confidence: 99%